NATURAL DISASTER: WATER PLAN AND JAI SHANKAR PRASAD'S SUCCESS: प्राकृतिक आपदा: जल प्लावन और जय शंकर प्रसाद की कामायनी - Rathi, Neelam (International Journal of Research -GRANTHAALAYAH, 2015)
When the events of graphical nature take extreme form, then the entire biological world including human beings gets into difficulty and a situation of destruction arises. Such incidents are sometimes so quick that it becomes difficult to recover. In the face of these events of nature, man becomes dwarf such as volcanoes, earthquakes and water floats etc. Although such events are born out of the normal process of nature, but some of the human responses to its depth and expansion become helpful, such as the exacerbation of seasonal events from forest destruction. Such disruptive natural phenomena are called natural disasters. Divine disasters caused by environmental imbalances disturb the biotic world. Loss from such outbreaks ever. Sometimes it is so fierce that despite all the scientific and technological development, the human kneels in front of them. These natural outbreaks are directly related to the environment. Those who have been running since time immemorial. But it is also true that due to increase in human numbers and prosperity due to these natural outbreaks, the effects of natural hazards are becoming more harmful. Thus we can say that today with the nature behind the natural outbreak. Human crisis is also associated with it. आलेख श्प्रकृति की घटनाएँ जब चरम रूप ग्रहण कर लेती हैं तो उनसे मानव सहित सम्पूर्ण जैव जगत कठिनाई में पड जाता है और विनाश की स्थिति उत्पन्न हो जाती है। ऐसी घटनाएँ कभी.कभी इतनी त्वरित होती हैं कि संभल पाना कठिन हो जाता है। प्रकृति की इन घटनाओं के सामने मनुष्य बौना हो जाता है जैसे ज्वालामुखीएभूकंप और जल प्लावन आदि। यूं तो ऐसी घटनाएँ प्रकृति की सामान्य प्रक्रिया से जन्म लेती हैंएलेकिन इनकी गहनता और विस्तार के लिए मनुष्य की कुछ अनुक्रियाएं सहायक बन जाती हैंए जैसे वन विनाश से मौसमी घटनाओं की उग्रता। ऐसी विघटनकारी प्राकृतिक घटनाओं को प्राकृतिक आपदाएपर्यावरणीय प्रकोप कहा जाता हैश्1। पर्यावरण असंतुलन से प्रकट होने वाली दैवीय विपत्तियाँ जैव जगत को अस्त व्यस्त कर देती है। ऐसे प्रकोपों से होने वाली हानि कभी. कभी इतनी भयंकर होती है की सारे वैज्ञानिक और तकनीकी विकास के बावजूद मानव इनके सामने घुटने टेक देता है। इन प्राकृतिक प्रकोपों का सीधा संबंध पर्यावरण से है। जिनका सिलसिला अनादिकाल से चला आ रहा है। लेकिन ये भी सच है कि इन प्राकृतिक प्रकोपों से मानव संख्या और समृद्धि में वृद्धि के कारण प्राकृतिक संकटों के प्रभाव अधिक हानिकारक होने लगे हैं। इस प्रकार हम कह सकते हैं कि आज प्राकृतिक प्रकोप के पीछे प्रकृति के साथ . साथ मानव जन्य संकट भी जुड़ा होता है।